Qisas: the theory and its application on women a comparison between civil and Islamic views - Muhammad Husni, Ahmad; Nasohah, Zaini; Mohammad, Abdul Basir; Mohd Nor, Amir Husin; Laluddin, Hayatullah; Samuri, Mohd Al-Adib; Che Omar, Nurhayati (Medwell Journal, 2014)
According to Islam, qisas is a form of punishment which is carried out on both men and women who commit crimes related to physical injury. The term qisas is not used in civil law but is instead replaced with the term tort as used in courts today. This article aims to discuss the view of scholars on qisas and its relation to civil law. The discussion is expanded through library research, using books, articles and internet resources on qisas, its application and the its differences from civil law especially on criminal tort law. The objective of this study is to find a suitable alternative which can be carried out on criminals, with special attention to female criminals in both civil and syariah laws. A comparison between these two aspects of law is used as the basis for finding the differences and similarities of their application. An in-depth study on the sources found that there are differences in the application of civil and syariah law, though their purpose remains the same. It is hoped that this paperwork will help readers in understanding the meaning of qisas.